(untitled) (Journal of Enam Medical College, 2013)
Diabetes mellitus is a public health problem in both developed and developing countries and has increased alarmingly, giving the disease the dimension of an epidemic. The aetiology of diabetes is multifactorial involving genetic, environmental, and behavioural origins. Exercise is an important part for the management of diabetes mellitus. Regularly planned exercise reduces insulin resistance, improves glucose tolerance, improves lipid profile and increases cardiovascular and cardiopulmonary function. This article critically reviews the more relevant evidence on the interrelationships between exercise and diabetes mellitus. This study included bibliography research from both the review and the research literatures on exercise in diabetes mellitus. From this review it appears that the effects of aerobic exercise are well established, and interventions with more vigorous aerobic exercise programmes resulted in greater reductions in HbA1c, greater increase in oxygen consumption and greater increase in insulin sensitivity. Considering the available evidence, it appears that resistance training could be an effective intervention to help glycaemic control, especially considering that the effects of this form of intervention are comparable with what is reported with aerobic exercise. It is well established that physical activity produces general and specific health benefits for diabetic patients. The basic principles of an effective exercise programme are the intensity, duration and frequency of exercise in an appropriate environment. Usually, moderate-intensity and long-duration exercise programmes are considered most suitable for diabetic patients. As it is supported by published evidence, encouragement to adopt increased physical activity and reduction of sedentary behaviour is a successful public health approach for diabetes mellitus prevention and management. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 99-108 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16133